Avocado Juice and Changes in Total Cholesterol and Triglyceride Levels among Depot Medroxyprogesterone Acetate Contraceptive Acceptors: A Quasi-Experimental Study - Liberty Barokah; Dewi Zolekhah; Tyas Ning Yuni Astuti Anggraini (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Depot medroxyprogesterone acetate (DMPA) is a widely used progestin only injectable contraceptive that has been associated with changes in lipid profiles and a potential increase in cardiovascular risk among women of reproductive age. Avocado is a nutrient dense fruit rich in monounsaturated fatty acids, fibre, and phytosterols, which may improve blood lipids and support cardiovascular health. This study aimed to explore the short term association between avocado juice consumption and changes in total cholesterol and triglyceride levels among women using progestin based injectable contraceptives. Methods: A quasi experimental pretest–posttest control group design was used. DMPA users were allocated to an intervention group that received avocado juice plus a high-cholesterol diet, or to a control group that received only the high-cholesterol diet, for 14 consecutive days. Total cholesterol and triglyceride levels were measured before and after the intervention. Data were analysed using normality tests, followed by paired t-tests and independent t-tests, and between-group comparisons were based on changes from baseline. Results: After 14 days, the intervention group showed a greater reduction in mean total cholesterol than the control group, indicating a possible association between avocado juice consumption and lower total cholesterol among DMPA users. In contrast, triglyceride levels decreased in both groups but did not differ significantly between them, and most triglyceride values remained within the normal range. The observed between group differences were modest and should be interpreted cautiously in light of the quasi experimental, non randomized, short term, and unblinded design. Conclusion: In this exploratory study, avocado juice consumption was associated with a short term reduction in total cholesterol levels among DMPA injectable contraceptives acceptors, whereas triglyceride levels did not change significantly between groups. These preliminary findings require confirmation in larger randomized controlled studies with longer follow up, stricter dietary control, and baseline adjusted analyses before firm conclusions can be drawn.